PENGEMBANGAN KOMIK SEBAGAI MEDIA PEMBELAJARAN FISIKA UNTUK SISWA SMA - Mutoharoh Mutoharoh; Razali Razali; Hadi Nasbey (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2012)
"The development of comics as a medium of learning physics for high school students". Teaching and learning processes in schools using teaching materials. One of the teaching materials used in schools are generally in the form of text books. High school student interest in reading books on physics books category is still relatively low. It can be seen from the data analysis of needs in senior high school that held in January 2012 with results as much as 63.49% of respondents spend the time to read a physics book for only 1-2 hours in one week, as much as 23.80% of respondents spent time reading physics books within 34 hours for one week, as much as 12.69% of respondents spent time reading physics book in 5-7 hours and the rest 0% of respondents spent time reading physics book more than 10 hours in a week. Based on these data it is clear that students' interest in reading text books, especially textbooks of physics is very low and will impact negatively on the development of student achievement, especially inphysics. To overcome this problem, was made innovations in instructional media. One innovation is make comics. The development comics using the methods of research and development to the stage: analysis of needs, product development and trials of product. The quality of media according to media experts from the comic display design, typography comics, comic content design, language, content, plot and summary the average percentage of 80.22%. The quality of media according to the material experts aspect of the feasibility of content, language, and presentation the average percentage of 89.55%. The quality of media according to the teachers and students are also very good in the category with the average percentage of 82.66% and 83.75%. Based on this research, the instructional media in the form of comic physics on the subject of optical instruments can be used as an alternative learning media for X-class high school semester2. Keywords: development, comics, media, learning, physical.